2003
DOI: 10.1007/s11661-003-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tensile prestrain on the notch toughness of low-alloy steel

Abstract: Tensile prestrains of various levels were applied to blank steel specimens. Four-point bend tests of notched specimens at various temperatures revealed an appreciable drop in the notch toughness of the specimens, which experienced 3 pct tensile prestrain. Further prestrains of up to 20 pct had a negligible effect on the notch toughness despite additional increases in the yield strength. Microscopic analyses combined with finite element method (FEM) calculations revealed that the decrease in toughness resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The results showed that the cleavage fracture initiation sites were located at both sides of the maximum principal tensile stress, but primarily on the left side (near to the notch) for low alloy steels and weld metals. [20][21][22][23][24]33,44] In the present work, it was found that the initiation sites were located in a zone where the triaxial-tensile stress elevated the yield stress to a level higher than the local fracture stress. The initiators can be the preferentially dangerous TiN inclusions in this zone.…”
Section: Characteristic Distancesupporting
confidence: 48%
See 1 more Smart Citation
“…The results showed that the cleavage fracture initiation sites were located at both sides of the maximum principal tensile stress, but primarily on the left side (near to the notch) for low alloy steels and weld metals. [20][21][22][23][24]33,44] In the present work, it was found that the initiation sites were located in a zone where the triaxial-tensile stress elevated the yield stress to a level higher than the local fracture stress. The initiators can be the preferentially dangerous TiN inclusions in this zone.…”
Section: Characteristic Distancesupporting
confidence: 48%
“…Detailed investigations have been conducted on the stress distribution when a Charpy V-notch (CVN) specimen is in the completely elastic state, and many useful results have been achieved, which can help explain TiN cleavage initiation at a characteristic distance away from the notch tip at low temperature. [19][20][21][22][23][24][25] However, in the case of room temperature, where considerable plastic fracture is present on the fracture surface, less attention has been paid to the behavior of TiN inclusions. Therefore, a study was made of this aspect and is reported in the present article, in which it is desired to increase the understanding of the behavior of TiN inclusions in cleavage fracture by analyzing the stress state variation during the fracture of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11,12] On the other hand, some researchers [24,25,26] suggested that the critical event can be changed from the propagation of a grain-sized crack through the propagation of a second-phase particle-sized crack to the nucleation of a crack by increasing the acuity of a defect [24,25] or decreasing the temperature. [26] In recent works, [27,28] it has also been found that with increasing grain sizes and decreasing second-phase particles, the critical event can be changed from the propagation of a grain-sized crack to a crack-nucleation-dominated model, [27] and increasing the prestrain and decreasing the temperature facilitates the critical event changing from the propagation of a nucleated microcrack to the nucleation of the microcrack and then deteriorates the toughness. [28] However, the question of whether the critical events for cleavage could be changed by various loading rates has not yet been clarified.…”
Section: A Effects Of Loading Rate On the Critical Event For Cleavagementioning
confidence: 99%
“…[26] In recent works, [27,28] it has also been found that with increasing grain sizes and decreasing second-phase particles, the critical event can be changed from the propagation of a grain-sized crack to a crack-nucleation-dominated model, [27] and increasing the prestrain and decreasing the temperature facilitates the critical event changing from the propagation of a nucleated microcrack to the nucleation of the microcrack and then deteriorates the toughness. [28] However, the question of whether the critical events for cleavage could be changed by various loading rates has not yet been clarified.…”
Section: A Effects Of Loading Rate On the Critical Event For Cleavagementioning
confidence: 99%
See 1 more Smart Citation